A study on serum cholinesterase level in organophosphorus poisoning and its correlation with severity of organophosphorus poisoning - Honnakatti, Vilas; Nimbal, Naren; Doddapattar, Prakash (International Journal of Advances in Medicine, 2018)
Background: There has been a steady increase in the use of organophosphates (OPs) as pesticides in most of the developing countries including India for more than 50 years. OPs tend to be the commonest cause of poisoning worldwide and are persistently and deliberately used in suicides in Agrarian areas. As stated by WHO, 3 million cases of pesticide poisoning occur every year, of these about 1 million are accidental and 2 million are suicidal poisonings, resulting in more than 0.25 million deaths per year. As there is limited availability of facilities and resources in developing countries, all OP poisoning patients are not managed in intensive care units. Hence it is important to understand the clinical features and other factors that indicate severity of poisoning which should be identified in the initial examination. Methods: It was a hospital based prospective study of 100 OP poisoning patients that were attending to casualty of BIMS Hospital and Medical College Belagavi, India. Over a period, patients fulfilling inclusion criteria were included and patients were categorized according to Peradeniya Organophosphorus Poisoning (POP) scale. Serum cholinesterase level measured at the time of admission. Results: The patients were in the age group of 18 to 70 years. Majority of the patients were in the age group of 21-30 years (51%). Sixty nine percent of the patients were from rural areas and 38% of them were farmers. Sixty nine percent of patients were from low socioeconomic stratum. Major route of intake of poison was ingestion. Eighty four percent of patients consumed poison with a suicidal intent. In this study, authors observed that there is a significant correlation between the severity of poisoning categorized by the POP scale and the serum cholinesterase at the time of initial presentation of the patients (P<0.001). Conclusions: Present study concluded that significant correlation between the degree of derangement in serum cholinesterase level and severity of poisoning at the initial presentation. Higher the score on the POP scale, the greater was the degree of derangement in the serum cholinesterase level.